2014
DOI: 10.1097/sla.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Harvesting Device Type and Outcomes in Patients Undergoing Coronary Artery Bypass Surgery

Abstract: Objective To evaluate angiographic and clinical outcomes associated with open and closed tunnel dissection endoscopic vein harvesting (EVH) devices. Summary Background Data A previous PREVENT-IV analysis reported that EVH for coronary artery bypass graft (CABG) surgery was associated with worse outcomes compared with traditional vein harvesting; however, outcomes by EVH device type were not available. Methods Using data from the PREVENT-IV trial, we compared 1549 patients from 75 surgical sites who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…3,4 A recent publication from PREVENTIV suggests that the risk associated with EVH was not explained by the device type. 5 We completely agree that understanding the true impact of EVH on graft patency and clinical outcomes will require an adequately sized randomized trial with appropriate outcomes. To this end, we await the results of the ongoing Randomized Endo-Vein Graft Prospective (REGROUP) trial (clinicaltrials.gov identifier NCT01850082).…”
mentioning
confidence: 96%
“…3,4 A recent publication from PREVENTIV suggests that the risk associated with EVH was not explained by the device type. 5 We completely agree that understanding the true impact of EVH on graft patency and clinical outcomes will require an adequately sized randomized trial with appropriate outcomes. To this end, we await the results of the ongoing Randomized Endo-Vein Graft Prospective (REGROUP) trial (clinicaltrials.gov identifier NCT01850082).…”
mentioning
confidence: 96%
“…information regarding vein graft patency was obtained from CAGs performed in 10 patients prior to follow-up and information on vein graft patency was obtained from the autopsy report in one patient. cluded that this difference was not related to a specific EVH device (10). An increased vein graft failure rate following EVH was shown in a subset of patients undergoing angiographic follow-up at one year from the randomized On/Off Bypass (rOOBY) trial which evaluated differences in clinical outcomes between patients undergoing on-and off-pump CABG (9).…”
Section: Vein Graft Failurementioning
confidence: 96%
“…Similar to the PrEVEnT iV study (10) in which there were no protocol requirements for pre-harvest use of heparin, all grafts in the present study were harvested by the EVH technique without heparinization. Lack of pre-procedural heparinization may, however, result in residual clot strands in the vein grafts and have the potential to decrease vein graft patency rates.…”
Section: Vein Graft Failurementioning
confidence: 99%
See 1 more Smart Citation
“…However, previous investigations of two databases, where many patients were enrolled, revealed that the endoscopic technique was associated with an increased long-term mortality rate and a higher rate of vein graft failure [9,10]. Contrarily, other studies reported that the endoscopic technique was not associated with a higher rate of vein graft failure and an increased mortality rate [11][12][13].…”
Section: Introductionmentioning
confidence: 99%